Salivary Biomarkers as Predictors of Obesity and Intermediate Hyperglycemia in Adolescents - Alqaderi, Hend; Hegazi, Fahad; Al-Mulla, Fahd; Chiu, Chung-Jung; Kantarci, Alpdogan; Al-Ozairi, Ebaa; Abu-Farha, Mohamed; Bin-Hasan, Saadoun; Alsumait, Aishah; Abubaker, Jehad; Devarajan, Sriraman; Goodson, J. Max; et al. (Frontiers in Public Health, 2022)
Introduction Childhood obesity presents a major risk for metabolic diseases in adulthood. Noninvasive methods are needed for predicting the course of obesity in children and its complications. Using blood for longitudinal analyses of biomarkers to predict disease in children is not a convenient method. Saliva presents a noninvasive platform to detect inflammatory changes in biomarkers as possible predictive measures of future pathological events. Objectives The aim of this study was to evaluate the relationship between specific salivary biomarkers, obesity, and intermediate hyperglycemia in children. We also investigated the longitudinal association between the salivary biomarkers and change in Body Mass Index-for-age percentile scores (BMIz). Methods Data on 353 adolescents were collected from the individuals recruited for seven years in an ongoing Kuwait Healthy Life Study cohort. BMIz was measured at 10, 12, and 17 years of age. Interleukin (IL)-6, IL-8, IL-10, Leptin, C-Reactive Protein (CRP), Insulin, Vascular Endothelial Growth Factor (VEGF), and Monocyte Chemoattractant Protein-1 (MCP-1) were measured in saliva and serum. Additionally, fasting blood plasma glucose levels were recorded. Multilevel longitudinal regression modeling, mediation analyses, and logistic regression were used to determine the predictive value of salivary biomarkers in obesity and hyperglycemia. Results Longitudinal analyses showed that with each one-unit increase of salivary CRP and insulin, there was a 3.5 kg/m2 and 3.2 kg/m2 increase in BMIz, respectively. Comparable to serum CRP and insulin, higher salivary CRP and insulin OR 4.94 [95%CI: 1.66,14., OR 2.64 [95%CI: 1.09, 6.38], respectively) were predictive of hyperglycemia and obesity (OR 4.53 [95%CI: 2.40,8.50], OR 3.29 [95%CI: 1.82,5.97], respectively). Insulin was a strong mediator in the relationship between obesity and hyperglycemia. Conclusion Our findings demonstrated that salivary CRP and insulin were associated with hyperglycemia, obesity, and possibly diabetes in adolescents. Salivary biomarkers are a noninvasive approach with significant value for disease risk assessment and prevention.